Exploring the educational potential of the Digital Story in a Nicaraguan Context (Revista Científica Estelí, 2015)
This study has as main objective to explore the educational potential of the digital story method in a Nicaraguan context. For this reason, in this study the origin of the digital story concepts and pedagogical text were presented. In addition, the perception of seventeen students of Educational Sciences, of the Regional Multidisciplinary Faculty Estelí (UNAN- FAREM- Estelí) about the educational value of digital story in their own workplaces, with their own students was investigated.In order to present the method of digital story to Nicaraguan students, a digital story workshop was implemented, in one of the laboratories of the faculty. Also, a questionnaire was applied to obtain the point of view of the participants about this form of telling stories as a teaching text. The main results show that students see a real potential in this method as an educational tool, and also they see it as something innovative in their educational performance.Keywords: digital, digital storytelling and educational text Story